Sperm whales forage year-round in the ross sea region - Giorli, Giacomo; Pinkerton, Matthew H. (Frontiers in Remote Sensing, 2023)
We investigated the seasonal and spatial occurrence of sperm whale (Physeter macrocephalus) in the Ross Sea region of the Southern Ocean derived from passive acoustic data. Two Autonomous Multichannel Acoustic Recorders (AMARs) moored about 10 m above the seabed were deployed in the austral summer of 2018 and recovered one year later. The northern AMAR (A3) was located on the Pacific-Antarctic Ridge at 63.7°S and the southern AMAR (A1) at 73.1°S on the Iselin Bank, part of the continental slope of the Ross Sea. Sperm whale echolocation signals were detected using signal processing scripts and validated by visual inspection of spectrograms. Our results demonstrate that sperm whales are present in the Ross Sea region year-round. At A1, sperm whale vocalisations were detected in every month between February and November, but absent in December and January. Whales were detected most often in February with an average of 0.310 detections per hour. Sperm whale vocalisations were detected at station A3 in every month except February when we had no observations. Our results contrast to a paucity of reported sightings of sperm whales from fishing and research vessels in the Ross Sea region between December and February. Probabilities of detecting sperm whales at A3 were on average 14.2 times higher than at A1 for the same month and monthly mean detections per hour were an average of 74.4 times higher at A3 than A1. At A1, we found a significant preference for day-time foraging rather than during the night or nautical twilight. In contrast, at A3, no clear day/dusk/night/dawn differences in sperm whale occurrence were found. Low sea-ice concentration (<80%) and open water within ~50 km were necessary but not sufficient conditions for higher detection rates of sperm whales (> 0.1 detections per hour). Overall, our research provides baseline information on sperm whale occurrence and establishes a method to track long-term change to help evaluate the conservation value of the Ross Sea region Marine Protected Area.